Pterygium and associated factors among adults: a hospital-based prospective study - Chhimi Wangmo; Nor Tshering Lepcha (Bhutan Health Journal, 2021)
Introduction: The aim of this hospital-based study was to assess the prevalence and associated factors of pterygium among adult patients visiting the Ophthalmology Outpatient Department (OPD) in the Jigme Dorji Wangchuck National Referral Hospital (JDWNRH), Thimphu.